Bronchial carcinoid: A propósito de una observación. - Perrone Noceti, Luis; Perrone Noceti, Luis; Laviña Risso, Raúl; González Moreno, Yamandú; Manaro, Julio (Cirugía del Uruguay, 1981)
A case of carcinoid tumor of the bronchi with a carcinoid syndrome is presented. Diagnosis was clinical and endoscopic and the treatment surgital excision.